2016
DOI: 10.1007/s10597-016-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

OCD Taboo Thoughts and Stigmatizing Attitudes in Clinicians

Abstract: Individuals who suffer from obsessive-compulsive disorder have persistent intrusive thoughts that cause severe distress that impairs daily functioning. These individuals often conceal their intrusive thoughts and delay help-seeking for fear of being stigmatized. Stigma can be problematic when it is present among mental health professionals because they may distance themselves from their clients and have a negative outlook on treatment outcome. To date there has not been any research that focuses on stigma that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The studies conducted by Simonds and Thorpe (2003) and Cathey and Wetterneck (2013) unintentionally oversampled women undergraduate students and aimed to generalize conclusions to the lay public broadly. Alternatively, although other studies appeared to oversample women (Samari et al, 2018;Steinberg & Wetterneck, 2017), considerations about their population of interest (i.e., nursing students and clinical psychologists/graduate students) revealed appropriate sample characteristics to generalize conclusions.…”
Section: Methodological Evaluationsmentioning
confidence: 98%
“…The studies conducted by Simonds and Thorpe (2003) and Cathey and Wetterneck (2013) unintentionally oversampled women undergraduate students and aimed to generalize conclusions to the lay public broadly. Alternatively, although other studies appeared to oversample women (Samari et al, 2018;Steinberg & Wetterneck, 2017), considerations about their population of interest (i.e., nursing students and clinical psychologists/graduate students) revealed appropriate sample characteristics to generalize conclusions.…”
Section: Methodological Evaluationsmentioning
confidence: 98%
“…A differential diagnosis should be primarily made with pedophilia: the sexual arousal derived from recurrent fantasies, sexual urges or behaviours involving prepubescent children, that could, or not, involve the sexual abuse of children. 2 There are clinical distinctions between these entities [11][12][13][14] : the first is the ego-dystonic and marked suffering in patients with P-OCD, contrary to most pedophiles that present pleasure when imagining sexual acts with children. Besides, they enjoy being near children and experience sexual gratification when engaging in grooming activities.…”
Section: Discussionmentioning
confidence: 99%
“…15 Likewise, individuals with obsessive thoughts from different symptom dimensions might avoid the disclosure of sexual obsessions, even after disclosing other types of intrusive thoughts, because they are perceived as less acceptable: Cathey (2013) found that the disclosure of an intrusive thought relating to a sexual theme was associated with more social rejection than the disclosure of a contamination-related intrusive thought. 3 Thus, it is important that healthcare providers normalise these types of concerns when interviewing OCD patients: Steinberg, 14 in a study about stigmatising attitudes in clinicians, found that, when engaging with professionals with cognitive-behavioural backgrounds, participants were more likely to socially reject or be concerned about individuals with obsessions related with contamination, harming, and sexual obsessions than those with scrupulous obsessions, and that they would be less likely to reveal sexual obsessions to others if they were experiencing those rather than the other three types of obsessions.…”
Section: Discussionmentioning
confidence: 99%
“…Willingness‐to‐treat ratings were high overall, though willingness was lower for weapons‐related exposures, and for sexual exposures in youth. The lack of SNC and relatively high willingness‐to‐treat ratings are encouraging as unacceptable thought OCD symptoms are common (Fernández de la Cruz et al, 2013; Williams et al, 2011) and have been associated with greater stigma by therapists (Steinberg & Wetterneck, 2017).…”
Section: Discussionmentioning
confidence: 99%